WHAT YOU EXPERIENCE IS WHAT YOU GET (WYXIWYG). - Lee, Gun A.; Kim, Gerard J.; Billinghurst, Mark (Communications of the ACM, 2005)
In this article, the author describes the term "What You experience is What You Get" (WYXIWYG) that has been coined to describe the merits of immersive authoring, putting content artists in the drivers seat of the production and providing a means of communicating with programmers to help them realize their ideas. The main challenge in immersive authoring is how to apply WYXIWYG and direct interaction methods in 2D graphical user interfaces to creating immersive content. Due to the limitations of its functions and hardware, more immersive authoring research is needed before the first commercial systems would be available. The authors are collecting and evaluating more results from case studies and user studies to further understand the advantages and disadvantages of immersive authoring. They will also add more complex logic-box functionality and explore how to support text and keyboard input. Immersive authoring with WYXIWYG features will play an important role in future virtual reality content production, helping popularize virtual and mixed-reality content by transferring more of the expressive power in content creation to artists, domain experts, and end users.